Oxidation of amorphous HfNbTaTiZr high entropy alloy thin films prepared by DC magnetron sputtering - Hruška, Petr; Lukáč, František; Cichoň, Stanislav; Vondráček, Martin; Čížek, Jakub; Fekete, Ladislav; Lančok, Ján; Veselý, Jozef; Minárik, Peter; Cieslar, Miroslav; Melikhova, Oksana; Kmječ, Tomáš; et al. (Journal of alloys and compounds, 2021)
High entropy alloys represent a new type of materials with a unique combination of physical properties originating from the occurrence of single-phase solid solutions of numerous elements. The preparation of nanostructured or amorphous structure in a form of thin films promises increased effective surface and high intergranular diffusion of elements as well as a high affinity to oxidation. In this work, we studied HfNbTaTiZr thin films, deposited at room temperature by DC magnetron sputtering from a single bcc phase target. Films exhibit cellular structure (∼100 nm) with fine substructure (∼10 nm) made of round-shape amorphous clusters. The composition is close to equimolar with slight Ti enrichment and without any mutual segregation of elements. Oxidation at the ambient atmosphere leads to the formation of Ti, Zr, Nb, Hf, and Ta oxide clusters in the film up to the depth of 200–350 nm out of the total film thickness of 1650 nm. Oxygen absorption takes place preferentially in the large vacancy clusters located in between the amorphous cluster aggregates. The dominant type of defect are small open volumes with a size comparable with vacancy. The distribution of these defects is uniform with depth and is not influenced by the presence of oxygen in the film. •Amorphous HfNbTaTiZr high entropy alloy thin films were deposited by DC magnetron sputtering.•A fine structure of round-shaped amorphous clusters ∼10 nm was observed.•Oxidation at ambient atmosphere leads to a preferential formation of Ti-, Hf- and Zr- oxide nanoclusters.•Oxidation takes place predominantly in large open volumes in between cluster aggregates.